2019
DOI: 10.1021/acs.jpcc.9b00005
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Twisting Motion of Organic Linkers via Concentration and Hydrogen-Bond Formation

Abstract: Benzothidiazole dibenzoic acid derivative (BTDB) is a well-known organic linker in various metal-organic framework structures as well as a fluorescent probe in biological systems. Here, we demonstrate that the radiative and non-radiative decay channels of BTDB can be interplayed and precisely controlled through concentration and hydrogen bond interactions as directly evidenced experimentally and theoretically. This leads to excited-state structural changes that significantly suppress the torsional motion aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…It is worth to mention that formations of molecular aggregates have been found to be responsible for many inconsistences in the reported optical absorption and emission values in the literature for coumarin dyes. [66][67][68][69] For example, if a coumarin dye is directly added to cyclohexane to prepare the solution (method A), or if the dye is first solubilized in very small amount of acetonitrile followed by diluted in cyclohexane (method B), the absorption values differ significantly due to formation of different extent of molecular aggregates. [68,69] Involvement of different charge transfer state of coumarin dyes in the excited state can be primarily unraveled through time resolved emission measurement.…”
Section: Solvatochromic Behavior Of Coumarin Dyesmentioning
confidence: 99%
“…It is worth to mention that formations of molecular aggregates have been found to be responsible for many inconsistences in the reported optical absorption and emission values in the literature for coumarin dyes. [66][67][68][69] For example, if a coumarin dye is directly added to cyclohexane to prepare the solution (method A), or if the dye is first solubilized in very small amount of acetonitrile followed by diluted in cyclohexane (method B), the absorption values differ significantly due to formation of different extent of molecular aggregates. [68,69] Involvement of different charge transfer state of coumarin dyes in the excited state can be primarily unraveled through time resolved emission measurement.…”
Section: Solvatochromic Behavior Of Coumarin Dyesmentioning
confidence: 99%
“… 12 Recently, it was shown that the TICT state stabilizes the charge separation in dye-sensitized solar cells (DSSCs) through small charge recombination rate. 4 , 13 16 For solar cell applications, a charge transfer process is designed to move from the donor to the acceptor moiety, forming an intramolecular charge transfer (ICT) state, 13 which is considered as a primary emissive state. Thus, the ICT state herein corresponds to the LE state in the traditional studied TICT molecules (see Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…This high EQY of BR α crystals is possibly due to restriction of the ultrafast isomerization process of BR, which increase the barrier for the conical intersection in the excited state, as previously shown in similar systems. 10 12 , 29 , 30 Moreover, we interpret this red-emission peak as coming from M1, whose S 1 state is lower in energy with respect to M2 (492 vs 384 nm for M1 and M2, respectively). Then, we report transient-emission data measured on the BR β crystals in Figure 3 b.…”
Section: Resultsmentioning
confidence: 85%
“…To determine the amount of active nonradiative channels, the emission of BR crystals has been measured at low temperature (77 K), and, as it is apparent in Figure 4 a, the emission intensity increases by a factor of 3, meaning that the EQY can reach ∼75%. This indicates that nonradiative decay channels are still active at room temperature for the α crystal, suggesting a residual activity of large-scale motions, 20 , 29 , 30 , 39 42 aggregation effects, 21 , 29 , 43 or heat dissipation by crystal phonons. 44 , 45 …”
Section: Resultsmentioning
confidence: 99%